Rhizobium Inoculation Experiment to Increase Soybean (Glycine max) Production in Horticulture Learning - Dewa Nyoman Oka; Herry Maurits Sumampouw; Ni Nyoman Serma Adi (Westscience Press, 2026)
The purpose of this study was to determine: (1) whether Rhizobium inoculation has an effect on soybean production; (2) whether the use of experimental methods in horticulture learning can improve learning outcomes? This experimental research used a simple posttest only control group design. The data obtained in the form of soybean production (wet seed weight) were tested for normality and homogeneity. The normality test was carried out using Kolmogorov-Smirnov and Shapiro-Wilk statistics. If the normality requirements have been met, a parametric analysis using the t-test was conducted. To test whether the experimental method in horticulture learning can improve learning outcomes, Classroom Action Research (CAR) was used. The data collection technique used a learning outcome test instrument in each cycle. The collected data were then processed using a quantitative descriptive method. From the analysis, it can be concluded that: (1) Rhizobium inoculation on soybean seeds can increase soybean production compared to without Rhizobium inoculation. (2) Students learning outcome after using the experimental method continued to increase from the sufficient category (60.30) in the initial reflection, to the good category (72.60) in cycle I and excellent (87.60) in cycle II.